Role and Mechanism of PKC-δ for Cardiovascular Disease: Current Status and Perspective - Miao, Li-na; Pan, Deng; Shi, Junhe; Du, Jian-peng; Chen, Peng-fei; Gao, Jie; Yu, Yanqiao; Shi, Da-Zhuo; Guo, Ming (Frontiers in Cardiovascular Medicine, 2022)
Protein kinase C (PKC) is a protein kinase with important cellular functions. PKC-δ, a member of the novel PKC subfamily, has been well-documented over the years. Activation of PKC-δ plays an important regulatory role in myocardial ischemia/reperfusion (IRI) injury and myocardial fibrosis, and its activity and expression levels can regulate pathological cardiovascular diseases such as atherosclerosis, hypertension, cardiac hypertrophy, and heart failure. This article aims to review the structure and function of PKC-δ, summarize the current research regarding its activation mechanism and its role in cardiovascular disease, and provide novel insight into further research on the role of PKC-δ in cardiovascular diseases.